FUNGSI HADITS TERHADAP AL-QUR`AN - Hamdani Khairul Fikri (TASÂMUH, 2015)
Hadith is the second Islamic law pillar after Al-Qur’an. Hadith as second source is showed by three things, namely: Al- Qur’an itself, agreement (Ijma’) of religious leader, logic (ma’qul). Al-Qur’an emphasizes that the messenger functions to explain meaning of commandment of Allah. Therefore, what he states mustbe followed and his attitude as prophet must be followed by allMuslims. This paper found that functions of hadith toward Al-Qur’an are explanation (bayan) and reinforcement (muhaqiq) for Al-Qur’an. Al-Qur’an is also as Explanation of reinforcement (Bayân taqrir), explanation of passages of Al-Qur’an or explanation of interpretation (Bayân tafsir), explanation of elaboration (Takhshîsh al-’âm), and explanation of change (Bayân Tabdîl). This paper not only found those things but also found that hadiths of the messenger have determined new regulation which is not determined by al-Qur’an. In al-Qur’an there are many verses which command to the faithful to be loyal and do what the messenger commands, forbids, and also threatens people who disagree with the hadith.